BASIC HEALTH UNIT IN URBAN AND RURAL CONTEXTS: CHALLENGES AND LIMITATIONS (REMUNOM, 2025)
This undergraduate thesis aims to analyze the main challenges faced by Basic Health Units (UBS) in the urban and rural areas of the municipality of Porto Velho – RO. The research is descriptive in nature and based on an experience report conducted at local UBS, seeking to identify inequalities in access to healthcare services. Among the problems identified, the insufficient supply of health services stands out, both in rural and urban areas, as well as the lack of materials, infrastructure, transportation and properly qualified professionals. The findings highlight a range of barriers that hinder the effectiveness and equity of healthcare services provided to the population, particularly in more vulnerable areas.